PELATIHAN PEMASARAN ONLINE BERBASIS DIGITAL UNTUK MENINGKATKAN PENJUALAN BISNIS ONLINE PADA UMKM KHAS COLLECTION DI DESA KARANGSARI KECAMATAN KARANGANYAR KABUPATEN PEKALONGAN - Fitri Virdha Amelia; Wulandari, Ayu; Wati, Vatika Dara; Fidela, Syahda; Adinugra, Hendri Hermawan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Increasing the sales of a product can be done in various ways, one of which is by utilizing online sites found on gadgets. However, not all entrepreneurs, including MSMEs, understand the management of online sites on gadgets, especially for MSMEs located in villages. One of these villages is Karangsari Village in the Khas Collection UMKM. Through online-based marketing training, it is hoped that it can provide strategies and insights for Khas Collection MSME players in utilizing digital as a means of sales. The purpose of this training is to increase product sales and increase the economic income of Khas Collection MSME entrepreneurs. The results obtained are that the Khas Collection MSMEs in Karangsari Village already have social media accounts such as Instagram and Shopee and have understood the features contained in the application, so that income and sales have increased.